Rancang Bangun Sistem Penggajian Karyawan Dengan Framework Laravel (Studi Kasus : PT.Techpolitan Indonesia Persada) - Karina Mawardah; Rinna Rachmatika (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
PT. Techpolitan Indonesia Persada is a company engaged in coding training and co-working space. The process of recording and calculating salaries applied by the company is still manual by MS. Excel program. This causes an error in calculating employee salaries and the process of printing payslips which takes a long time. In solving these problems, the authors designed a web-based employee payroll information system. In this design the author uses the PHP programming language with MySQL database format, uses the Waterfall Method and uses the Laravel Framework. With this system design, it is hoped that the company will find it easier to record, calculate and report employee payroll faster and more efficiently.